RADIOGRAPHIC EXAMINATION OF THE CRANIUM USING POSTEROANTERIOR (PA) AND LATERAL PROJECTIONS IN PATIENTS WITH CLINICAL TUMOR FINDINGS AT IBNU SINA ISLAMIC HOSPITAL, PEKANBARU - Ghea Aprillia; Wenda Erliyanda; Teguh Ilhami (Medical Imaging and Radiation Protection Research Journal, 2025)
The head or skull functions as a protective structure for the brain and serves as an attachment site for facial organs such as the eyes, nose, ears, and other structures. The skull is divided into two main parts: the facial skeleton and the cranial skeleton. One of the indications for cranium radiographic examination is the presence of a tumor in the mandibular region. A tumor is a group of abnormal cells formed as a result of excessive and uncoordinated cell division. This study employed a descriptive qualitative method using a case study approach involving a patient diagnosed with a mandibular tumor in the Radiology Department of Ibnu Sina Islamic Hospital, Pekanbaru. During data collection, the researcher conducted observations and interviews with the radiographer responsible for performing the cranium examination. The results showed that the cranium radiographic examination for a tumor case was performed using Posteroanterior (PA) and Lateral projections. In the radiographic examination procedure conducted at the Radiology Department of Ibnu Sina Islamic Hospital, Pekanbaru, several differences were found compared with the theory presented in Merrill’s Atlas of Radiographic Positioning and Procedures. According to the atlas, cranium examinations are generally performed using Anteroposterior (AP) and Lateral projections. However, at Ibnu Sina Islamic Hospital, Pekanbaru, PA and Lateral projections were utilized. Despite this difference, the projections used were considered sufficient to provide optimal diagnostic information.